Impaired semantic memory during acute transient global amnesia - Sandikci, Vesile; Ebert, Anne; Hoyer, Carolin; Platten, Michael; Szabo, Kristina (The journal of neuropsychology, 2022)
As a clinical model of hippocampal dysfunction, transient global amnesia (TGA) causes reversible memory disturbance. While episodic memory deficits in TGA patients have been extensively described, data regarding semantic memory involvement are sparse and contradictory. We report impaired semantic fluency performance in 16 patients with hippocampal lesions on MRI during acute TGA compared to their performance one day later and to that of 20 healthy subjects. Our findings support the involvement of the hippocampus in semantic retrieval.
First published: 21 May 2021
Gesehen am 27.10.2023